Evaluating Alternative Feed Additives: The Role of Caulerpa race-mosa and Probiotics in Enhancing Catfish (Clarias gariepinus) Aqua-culture Performance - muchdar, Fatma; Juharni; Abdullah, Nursanti; Khairun Nisaa; Suryani, Suryani; Sudrajat, Iman (Department of Aquaculture, 2026)
This study evaluated the effects of Caulerpa racemosa and probiotics on the growth performance, survival, and feed utilisation of African catfish (Clarias gariepinus) fingerlings. Four treatments were formulated: A (25g C. racemosa + 6mL probiotics), B (50g C. racemosa + 6mL probiotics), C (75g C. racemosa + 6mL probiotics), and D (control, no additives). The highest weight gain (27.80±1.62g) and most efficient feed conversion ratio (FCR) were observed in the control group, attributed to its optimal protein (17.82%) and fat (10.51%) content. Treatment A yielded moderate growth (19.35±2.45g) with the lowest FCR (1.62±0.03), indicating a potential synergistic effect of low-level C. racemosa and probiotics. In contrast, Treatments B and C resulted in reduced growth (17.72±0.47g and 16.92±1.09g, respectively), likely due to high levels of dietary carbohydrate (up to 61.56%) and ash (up to 24.25%), which impaired nutrient assimilation. Survival rates were uniformly high across treatments (93.3–100%), confirming the safety of these additives. The findings underscore the importance of dosage in functional feed formulations, highlighting that excessive seaweed inclusion may compromise performance, while low-level supplementation in combination with probiotics offers promising benefits for sustainable aquaculture.